2011
DOI: 10.1103/physrevb.83.220503
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature surface superconductivity in topological flat-band systems

Abstract: We show that the topologically protected flat band emerging on a surface of a nodal fermionic system promotes the surface superconductivity due to an infinitely large density of states associated with the flat band. The critical temperature depends linearly on the pairing interaction and can be thus considerably higher than the exponentially small bulk critical temperature. We discuss an example of surface superconductivity in multilayered graphene with rhombohedral stacking.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
489
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(512 citation statements)
references
References 24 publications
19
489
1
3
Order By: Relevance
“…This type of 2D flat bands is proposed as a novel route to achieve high temperature superconductivity. 47,48 When the SOC is included, three node lines are gapped out and evolve into a pair of Dirac points along the M−R line, thus the NLS becomes a 3D DSM. There is a bulk Dirac node projected on the M point (the red dot) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of 2D flat bands is proposed as a novel route to achieve high temperature superconductivity. 47,48 When the SOC is included, three node lines are gapped out and evolve into a pair of Dirac points along the M−R line, thus the NLS becomes a 3D DSM. There is a bulk Dirac node projected on the M point (the red dot) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29] Such a 2D flat band surface state may become a route to achieve high temperature superconductivity. 47,48 As a result, it is of great impetus to search new NLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…flat band high temperature superconductivity, 25,26,28 various magnetic orders 29 etc. Under an applied magnetic field, a Lifshitz transition induced by trigonal warping in rhombohedral trilayer graphene has been reported.…”
mentioning
confidence: 99%
“…Flat-band ferromagnetism has been studied first by Lieb [16] and, subsequently, by Tasaki and Mielke [17][18][19][20]. More recently it has been shown that the high density of states of flat bands enhances the superconducting critical temperature [21,22]. Indeed, for fixed interaction strength, the flat-band dispersion provides the maximal critical temperature within mean-field BCS theory [23].…”
mentioning
confidence: 99%